Anti-Corrosive Substance as Green Inhibitor for Carbon Steel in Saline and Acidic Media. Issue 1 (March 2021) - Al-Mashhadani, Haider Abdulkareem; Alshujery, Mohannd Kadhim; Khazaal, Fatma A.; Salman, Ali M.; Kadhim, Mustafa M.; Abbas, Zaid M.; Farag, Sajad K.; Hussien, Hasan Fadhil
Abstract: Ficus (FIC) leaf extract used as corrosion inhibitor for carbon steel alloy (C.S) in two corrosive environments (saline and acidic) with four concentrations (1, 2, 3 and 4 ppm) at varied temperature range between (298-328 K) using electrochemical polarization measurements. The importance of this work focused on the use the green chemistry that is far from the chemical materials effect. The results of polarization presented the FIC inhibitor consider a mixed type (anodic and cathodic) inhibitor. Tafel curve used to evaluate the corrosion inhibition activity. In a saline medium, the best inhibitor efficiency reaches to (87%) in 2 ppm and IE% reach to (99%) for HCl medium inhibited by 1ppm. Langmuir isotherm obeys the study by thermodynamic parameters and confirms the physical adsorption.